High performance disability sport coaching - Kohe, Geoffery Z. 1983-; Peters, Derek M. (Routledge, 2017)
As the profile of disability sport has risen, so has the emphasis grown beyond participation to include the development of a high performance environment. This book is the first to take an in-depth look at the role of coaches and coaching in facilitating the professionalisation of disability sport, in raising performance standards, and as an important vector for the implementation of significant political, socio-cultural and technological change. Using in-depth case studies of elite disability sport coaches from around the world, the book offers a framework for critical reflection on coaching practice as well as the reader's own experiences of disability sport. The book also evaluates the vital role of the coach in raising the bar of performance in a variety of elite level disability sports, including athletics, basketball, boccia, equestrian sport, rowing, soccer, skiing, swimming and volleyball. Providing a valuable evidence-based learning resource to support coaches and students in developing their own practice, High Performance Disability Sport Coaching is essential reading for all those interested in disability sport, coaching practice, elite sport development and the Paralympic Games.